Uncertainty increases neural indices of attention in obsessive‐compulsive disorder. Issue 11 (25th May 2017) - Dieterich, Raoul; Endrass, Tanja; Kathmann, Norbert
Abstract : Background: Patients with obsessive‐compulsive disorder (OCD) experience abnormally high levels of uncertainty, and unpredictability is evaluated negatively and not well tolerated. The current study examined neural correlates of attentional processing in response to experimentally induced uncertainty in OCD. Methods: Twenty‐four OCD patients and 24 healthy controls performed a task where neutral and negative pictures were preceded by a cue, either being predictive (certain condition) or nonpredictive (uncertain condition) of subsequent picture valence. We examined prepicture anticipatory attention through α (∼8–12 Hz) suppression, and attentional allocation during picture presentation with the P1, N1, P2, N2, and late positive potential (LPP) of the event‐related potential. Additionally, we tested how clinical measures related to these attentional markers. Results: Subjectively, patients overestimated the frequency of negative pictures after nonpredictive cues. Patients, but not controls, showed upper α(10–12 Hz) suppression after nonpredictive and predictive negative cues relative to predictive neutral cues. Only patients showed increased P2 and decreased N2 amplitudes for pictures after nonpredictive cues, and, whereas both groups showed increased LPP amplitudes for pictures after nonpredictive cues, this modulation was more pronounced in OCD during the early LPP (<1, 000 ms). In patients, P2 and LPP amplitudes for negative pictures were associated positively with anxiety and negatively with depression. Conclusions: These results suggest that OCD patients process anticipation of inevitable and potential threat similarly and highlight the substantial motivational impact of uncertain events to OCD patients. Finally, the correlation with anxiety implies that anxiety represents the source of hypervigilance during uncertainty resolution.